Formation of fluorophores from the kynurenine pathway metabolite N-formylkynurenine and cyclic amines involves transamidation and carbon–carbon bond formation at the 2-position of the amine - Tomek, Petr; Palmer, Brian D.; Kendall, Jackie D.; Flanagan, Jack U.; Ching, Lai-Ming (Biochimica et biophysica acta, 2015)
Tryptophan catabolism along the kynurenine pathway is associated with a number of pathologies including cataract formation and cancer. Whilst the chemical reactions of kynurenine are well studied, less is known about the reactivity of its precursor N-formylkynurenine (NFK). We previously reported the generation of a strong fluorophore in an aqueous reaction of NFK with piperidine, and herein we describe its structure and mechanism of formation. Compounds were identified using NMR, mass and UV spectroscopic techniques. The products from the reaction of amines with amino acids were quantified using HPLC-MS. The novel fluorophore was identified as a tetrahydroquinolone adduct (PIP-THQ), where piperidine is N-formylated and attached at its 2-position to the quinolone. NFK is initially deaminated to generate an unsaturated enone, which forms an adduct with piperidine and is subsequently converted into the fluorophore. Testing of a variety of other secondary amines showed that only cyclic amines unsubstituted at both positions adjacent to nitrogen could form fluorophores efficiently. The amino acids tryptophan and kynurenine, which lack the formamide group do not form such fluorophores. NFK forms fluorophores in a not previously published reaction with cyclic amines. Our study is the first to provide evidence for concurrent transamidation and substitution at the 2-position of a cyclic amine occurring under moderately-heated aqueous conditions with no added catalysts. The high reactivity of NFK demonstrated here could result in formation of biologically relevant metabolites yet to be characterised. [Display omitted] •N-formylkynurenine (NFK) and cyclic amines react to form strong fluorophores.•Fluorophores are formed in an aqueous, uncatalysed reaction at moderate temperatures.•Amine is attached to tetrahydroquinolone scaffold of fluorophore via 2-position.•Amine moiety of the fluorophore is formylated at the nitrogen of the cyclic amine.•NFK could form yet unidentified biologically relevant metabolites.